343 A Randomised Trial of Two Techniques of Bottle Feeding for Preterm Infants. (October 2012) - Dawson, JA; Myers, LR; Moorhead, A; Jacobs, SE; Ong, K; Salo, F; Davis, PG
Abstract : Background and Aims: Preterm infants will begin the transition from tube to suck feeds at 34 weeks' corrected age. Our aim was to compare physiological stability in two positions for bottle feeding preterm infants, the "cradle hold" versus a "side-lying" position. Methods: Randomised crossover trial of infants < 34 weeks' gestation at birth, ≥ 34 weeks' corrected gestation at study, receiving ≥ two sucking feeds/day. Feeds were studied on successive days. A pulse oximeter (PO) measured oxygen saturation (SpO2 ) and heart rate(HR), before, during and for 30 minutes after feeds. Continuous data were compared with paired t-tests, proportions compared with Χ 2 . Results: 25 study infants were, mean (SD) 29(3)weeks gestation and 1158(479)g at birth and mean (SD) 37(2.4) wks corrected age and 2740 (589)g at study. Eight study infants were receiving oxygen or respiratory support. In these 8 infants 5/8 (62%) versus 7/8 (87%) in side and cradle feeding positions experienced a SpO2 < 80% (p=0.25) during study feeds. Conclusions: Little difference in physiological stability was seen between the two bottle feeding positions. Both methods may be appropriate for the transition from tube to bottle feeding in preterm infants.